The Mediating function of College Radio Programming in the City of Monterrey, Nuevo León (2020)
This article refers to a research on the social function of college radio in Mexico, which falls within the context of university media research. The theoretical approach of Manuel Martín Serrano and the mass communication model of professor Carlos Lozano were considered. The main objective of the research was to analyze the communicative mediation associated with the radio programming of three college radio stations (Radio UANL 89.7, Frecuencia TEC 94.9 and Radio UDEM 90.5) from the communicative perspective of the messages and the impact of the elements that they intervene in the construction of radio products, which are presented immediately under a classification of training, information, and entertainment. For researching the subject, a quantitative methodology was implemented, choosing “length of time” as an impact variable for the measurement of daily programming time, as well as the comparison of themes and communicative products projected by the broadcasting stations. The results indicate that the musical frame occupies between 60 % and 67 % of the programming. The generality shown in the radio programs lies in the homogeneity in programming schedules on the morning, because information contents monopolize most of spaces in the three stations, providing another option in quadrant that benefits the social function. The conclusions indicate a bet on diversification of programming and a communicative practice based on offering educative entertainment, showing a new space of interrelation as well as their understanding of the university’s identity development.